2007
DOI: 10.1007/s00401-007-0222-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical characterisation of sensory neurons infected in vitro with rabies virus

Abstract: This work was aimed at the morphological and biochemical characterisation of the most susceptible neuronal subpopulation to rabies virus (RABV) infection. Adult mouse DRG cultures were infected with RABV and double-processed for viral antigen detection and neuropeptides: calcitonin gene-related peptide (CGRP), galanin (GAL), substance P (SP), neuropeptide Y (NPY) and vasoactive intestinal peptide (VIP). It was found that 56% of the neurons in culture were small (diameter < 20 microm) but, in spite of this, 69%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…Similar to previous reports of DRG neurons in cultures (14,29), we have found that CVS infects only a subpopulation (33 to 54%) of DRG neurons. CVS infection did not cause a loss of neuronal viability over 72 h in CVS-infected DRG neurons above baseline levels observed with the mock-infected cultures.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to previous reports of DRG neurons in cultures (14,29), we have found that CVS infects only a subpopulation (33 to 54%) of DRG neurons. CVS infection did not cause a loss of neuronal viability over 72 h in CVS-infected DRG neurons above baseline levels observed with the mock-infected cultures.…”
Section: Discussionsupporting
confidence: 92%
“…We have studied CVS infection in cultured DRG sensory neurons because they are known to be relatively permissive to in vitro infection with rabies virus (2,14,(27)(28)(29), with survival of rabies virus-infected DRG neurons for more than 20 days without cytopathic effects observed with the cultures (27). Hence, DRG neurons are an amenable neuronal cell type for an assessment of changes in morphology and/or growth of their neurites (axons) in rabies virus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used cultured DRG neurons because these neurons are known to be relatively permissive to rabies virus infection (Castellanos et al, 2000;Martinez-Gutierrez and Castellanos, 2007;Tsiang et al, 1989Tsiang et al, , 1991Tuffereau et al, 2007), which facilitates evaluation of mechanisms of disease involving axons. DRG neurons from adult rodents are most suitable for the evaluation of neurites (axons).…”
Section: Cultured Dorsal Root Ganglion Neurons For Studying Neurmentioning
confidence: 99%
“…Our group has previously reported a neurotrophin antitranscriptional and antireplicative effect in dorsal root ganglion (DRG) neuron cultures infected with RABV (Castellanos et al, 2000;Castellanos et al, 2005;Martínez-Gutiérrez & Castellanos, 2007). These findings, plus results obtained more recently using cellular kinase inhibitors, have suggested cell machinery regulation of the function of proteins directly participating in viral transcription and replication events, among them being the P protein (unpublished results).…”
Section: Introductionmentioning
confidence: 62%